Effectiveness of CPNS Basic Training Building a Competent State Civil Apparatus - Pratidina, Ginung; Silpiya, Devi; Seran, G. Goris (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
The purpose of this research is to find out how the effectiveness of basic training for Civil Servant Candidates in building a competent state civil apparatus at the State Civil Apparatus Personnel Development Centre. This research uses descriptive research methods with a quantitative approach. With sample 80 people from the element of CPNS basic training participants. Data were collected through survey techniques through distributing questionnaires. Data analysis using a Likert scale. The results show that the overall response that the effectiveness of basic training for prospective civil servants at the staffing development centre of the state civil apparatus in the dimension of program objectives obtained a score of 4.44 in the